Study on the Utilization of Egg Shells as CO2 Adsorbent in the Combustion Process of Empty Palm Fruit Bunches - Pratama, Andrian Putra; Yerizam, Muhammad; Syarif, Aida (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
The problem of carbon dioxide (CO2) emissions from the combustion of biomass, such as empty palm fruit bunches (TKKS), is a significant challenge in climate change mitigation efforts. This research aims to examine the effectiveness of eggshells as a CO2 adsorbent in the combustion process of empty palm fruit bunches, and to analyze the effect of adding adsorbent mass on exhaust gas emissions. Eggshells were calcined at 900°C to produce calcium oxide (CaO), then characterized using XRD and Iodine Number tests, and tested in a CO2 adsorption system using gas flow. The XRD test results showed that calcined eggshells have a crystalline structure with a crystalline level of 93.54%, indicating the dominance of CaO compounds as the active component. The Iodine Number test yielded the highest value of 330.018 mg/g at a mass of 2 grams, which indicates good surface area and porosity. CO2 adsorption testing showed that an adsorbent mass of 15 grams was able to reduce CO2 concentration from 974 ppm to 212 ppm, while adding adsorbent mass above 30 grams did not provide a significant reduction due to the increasing initial CO2 concentration. Overall, the results of this study indicate that eggshells have the potential to be an effective, environmentally friendly, and organic waste-based CO2 adsorbent. Their utilization can be an alternative simple carbon capture technology for biomass combustion systems, while also supporting sustainable household waste management.